VD_FINDINFO AI 29/09 - 417/2010 vom 22. September 2010 - VD Tribunal cantonal (2010)
AIASSURANCE, PRESTATION D'ASSURANCEAI, RENTE D'INVALIDITÉ, FORCE PROBANTE, DEGRÉ DE L'INVALIDITÉ | 28 al. 2 LAI, 69 al. 1bis LAI, 83 LOJV, 16 LPGA, 57 LPGA, 61 let. g LPGA, 61 LPGA, 7 LPGA, 8 LPGA, 2 LPA-VD, 52 LPA-VD, 55 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. a LPA-VD